Pu(iii) and Cm(iii) in the presence of EDTA: aqueous speciation, redox behavior, and the impact of Ca(ii). Issue 15 (25th March 2022) - DiBlasi, Nicole A.; Tasi, Agost G.; Trumm, Michael; Schnurr, Andreas; Gaona, Xavier; Fellhauer, David; Dardenne, Kathy; Rothe, Jörg; Reed, Donald T.; Hixon, Amy E.; Altmaier, Marcus
Abstract : Combined advanced spectroscopy and solubility studies provide evidence for the formation of novel calcium-containing and hydrolyzed (Cm, Pu)(iii )–EDTA complex(es). Abstract : The impact of calcium on the solubility, redox behavior, and speciation of the An(iii )–EDTA (An = Pu or Cm) system under reducing, anoxic conditions was investigated through batch solubility experiments, X-ray absorption spectroscopy (XAS), density functional theory (DFT), and time-resolved laser fluorescence spectroscopy (TRLFS). Batch solubility experiments were conducted from undersaturation using Pu(OH)3 (am) as the solid phase in contact with 0.1 M NaCl–NaOH–HCl–EDTA–CaCl2 solutions at [EDTA] = 1 mM, pHm = 7.5–9.5, and [CaCl2 ] ≤20 mM. Additional samples targeted brine systems represented by 3.5 M CaCl2 and WIPP simulated brine. Solubility data in the absence of calcium were well-described by Pu(iii )–EDTA thermodynamic models, thus supporting the stabilization of Pu(iii )–EDTA complexes in solution. Cm(iii )–EDTA TRLFS data suggested the stepwise hydrolysis of An(iii )-EDTA complexes with increasing pH, and current Pu(iii )-EDTA solubility models were reassessed to evaluate the possibility of including Pu(iii )–OH–EDTA complexes and to calculate preliminary formation constants. Solubility data in the presence of calcium exhibited nearly constant log m (Pu)tot, as limited by total ligand concentration, with increasing [CaCl2 ]tot, which supports the formation of calcium-stabilized Pu(iii )–EDTA complexes in solution. XAS spectra without calcium showed partial oxidation of Pu(iii ) to Pu(iv ) in the aqueous phase, while calcium-containing experiments exhibited only Pu(iii ), suggesting that Ca–Pu(iii )–EDTA complexes may stabilize Pu(iii ) over short timeframes ( t ≤45 days). DFT calculations on the Ca–Pu(iii )–EDTA system and TRLFS studies on the analogous Ca–Cm(iii )–EDTA system show that calcium likely stabilizes An(iii )–EDTA complexes but can also potentially stabilize An(iii )–OH–EDTA species in solution. This hints towards the possible existence of four major complex types within Ca–An(iii )–EDTA systems: An(iii )–EDTA, An(iii )–OH–EDTA, Ca–An(iii )–EDTA, and Ca–An(iii )–OH–EDTA. While the exact stoichiometry and degree of ligand protonation within these complexes remain undefined, their formation must be accounted for to properly assess the fate and transport of plutonium under conditions relevant to nuclear waste disposal.